2002
DOI: 10.1101/lm.46502
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course of Neural Changes Underlying Auditory Perceptual Learning

Abstract: Improvement in perception takes place within the training session and from one session to the next. The present study aims at determining the time course of perceptual learning as revealed by changes in auditory event-related potentials (ERPs) reflecting preattentive processes. Subjects were trained to discriminate two complex auditory patterns in a single session. ERPs were recorded just before and after training, while subjects read a book and ignored stimulation. ERPs showed a negative wave called mismatch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
150
6
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(184 citation statements)
references
References 66 publications
24
150
6
4
Order By: Relevance
“…These effects are consistent with previous MEG and electroencephalographic studies that have shown neural changes characterized by enhanced responses to trained stimuli, presumably resulting from a larger cortical recruitment that occurs across multiple timescales of training ranging from a few minutes to several days (Cansino and Williamson, 1997;Pantev et al, 1999;Menning et al, 2000;Atienza et al, 2002;Bosnyak et al, 2004). The general finding of increased responses to the trained stimulus is also consistent with a long history of neurophysiological studies that have shown the existence of rapid cortical plasticity, in which minutes of classical or operant conditioning suffice to induce profound changes of neural responses and receptive field properties in primary auditory cortices (Galambos et al, 1956;Weinberger and Diamond, 1987;Buonomano and Merzenich, 1998).…”
Section: Discussionsupporting
confidence: 79%
“…These effects are consistent with previous MEG and electroencephalographic studies that have shown neural changes characterized by enhanced responses to trained stimuli, presumably resulting from a larger cortical recruitment that occurs across multiple timescales of training ranging from a few minutes to several days (Cansino and Williamson, 1997;Pantev et al, 1999;Menning et al, 2000;Atienza et al, 2002;Bosnyak et al, 2004). The general finding of increased responses to the trained stimulus is also consistent with a long history of neurophysiological studies that have shown the existence of rapid cortical plasticity, in which minutes of classical or operant conditioning suffice to induce profound changes of neural responses and receptive field properties in primary auditory cortices (Galambos et al, 1956;Weinberger and Diamond, 1987;Buonomano and Merzenich, 1998).…”
Section: Discussionsupporting
confidence: 79%
“…More recently, Ylinen and Huotilainen (2007) reported an enhanced N1 in the ERP elicited by vowels from the native language in contrast to language-unfamiliar vowels. Notably, an increase in the N1(m) and/or P2 response for non-intentionally processed sounds has also been observed intraindividually after acoustic discrimination training (e.g., Menning et al, 2000;Atienza et al, 2002;Tremblay and Kraus, 2002;Bosnyak et al, 2004). A similar increase in the P2 response observed after passive stimulus exposure (Sheehan et al, 2005) indicated that the observed effects were related to increased acoustic familiarity with the presented sounds.…”
Section: Introductionsupporting
confidence: 53%
“…The familiarity effects observed before 300 ms in the present study indicate that familiar sounds are already processed differently on low-level auditory processing stages, which could result in an increased dicriminability of familiar sounds. This would enhance deviancerelated components (e.g., Atienza et al, 2002). It seems that no familiarity-related effects on auditory deviance processing are triggered when the deviance is unrelated to the familiarity of the sounds.…”
Section: Location-deviant Processing For the Familiar And The Unfamilmentioning
confidence: 99%
“…The remarkable agreement with the present study is the identification of rapid and stimulus-specific adaptation of neural responses to repeated standards, whereas the response to deviants did not change with repetition. Some of the long-term adaptation effects displayed by those auditory neurons (Ulanovsky et al, 2004) may also have a counterpart in human ERP changes (enhanced P50 and P2) across a time scale of a few minutes (Baldeweg et al, 1999) and up to days (Atienza et al, 2002).…”
Section: Neurophysiology Of Auditory Sensory Memorymentioning
confidence: 99%